2018
DOI: 10.1002/slct.201800320
|View full text |Cite
|
Sign up to set email alerts
|

Au‐Mediated Composite In2S3–Au–BiVO4 with Enhanced Photocatalytic Activity for Organic Pollutant Degradation

Abstract: A ternary composite photocatalyst In2S3–Au–BiVO4 was fabricated by stepwise photo‐reduction and deposition−precipitation methods. It was found that the Au nanoparticles (NPs) were selectively anchored on the {010} facets of decahedral BiVO4 crystals due to the oriented accumulation of electrons during the photo‐reduction stage. Based on the strong interaction between S−Au, In2S3 was loaded on the surface of Au NPs on BiVO4 {010} facets. Photocatalytic degradations of organic contaminants Rhodamine B and phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…SEM image of (g) Au-BiVO 4 , (h) In 2 S 3 –Au-BiVO 4 and (i) HR-TEM image of In 2 S 3 –Au-BiVO 4 . Reproduced with permission from ref . Copyright 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Facet Engineering For Modification Of Charge Carrier Behavio...mentioning
confidence: 99%
See 1 more Smart Citation
“…SEM image of (g) Au-BiVO 4 , (h) In 2 S 3 –Au-BiVO 4 and (i) HR-TEM image of In 2 S 3 –Au-BiVO 4 . Reproduced with permission from ref . Copyright 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Facet Engineering For Modification Of Charge Carrier Behavio...mentioning
confidence: 99%
“…In contrast, BiVO4-Au@CdS with the randomly deposited Au (Figure 14d) and Au@CdS NPs (Figure 14e) on both {010} and {110} facet prepared by the chemical reduction method exhibited a relatively poor photocatalytic performance for 4-nonylphenol degradation compared with the selectively prepared BiVO4-Au@CdS, demonstrating the important role of facet-induced carrier separation in achieving excellent photocatalytic activity (Figure 14f). Likewise, as reported by Wu et al, 159 Au 3+ ions were deposited on the electron-rich BiVO 4 {010} facets through a photoreduction process (Figure 14g), followed by the deposition of In 2 S 3 on Au NPs to form In 2 S 3 −Au-BiVO 4 (Figure 14h,i). In this ternary system, Au NPs severed as the recombination center of photogenerated electrons from the CB of {010}-BiVO 4 and the holes from the VB of In 2 S 3 , which not only greatly facilitated the charge separation of individuals but also remained the strongly reductive electrons in the CB of In 2 S 3 and strongly oxidized holes in the VB of {110} facet mBiVO 4 , leading to the optimal photocatalytic performance for RhB and phenol degradation.…”
Section: Facet Engineering For Modification Of Charge Carrier Behavio...mentioning
confidence: 99%
“…These results reveal that Z-scheme can effectively enhance the photocatalytic property of AgBr-Ag-BiVO 4 {010}. Compared to our previous works, 40,41 the photocatalytic activity of AgBr-Ag-BiVO 4 {010} for degrading RhB is about 2 and 3 times as high as that of CdS-Au-BiVO 4 and In 2 S 3 -Au-BiVO 4 , respectively. Therefore, it can be concluded that it is a cheap and highefficiency strategy of using the cheaper Ag instead of Au as the junction to construct Z-scheme photocatalytic materials.…”
Section: Resultsmentioning
confidence: 57%
“…80−83 According to previous reports in the literature, the conduction band (CB) and valence band (VB) energy levels of AgBr are −0.57 eV (vs SHE) and 2.18 eV (vs SHE) 84,85 and those of BiVO 4 are estimated to be 0.34 eV (vs SHE) and 2.74 eV (vs SHE), respectively. 86,87 If AgBr-Ag-BiVO 4 {010} is a traditional composite semiconductor, the migrate pathway of electrons should be from the AgBr CB to the BiVO On the basis of the above experimental results and analyses, we proposed the photocatalytic mechanisms of bacterium inactivation and organic pollutant degradation over AgBr-Ag-BiVO 4 {010}. As illustrated in Figure 11, after absorbing visible light, both BiVO 4 and AgBr can produce holes on their VB and electrons on their CB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation